2007
DOI: 10.1007/s11270-007-9388-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Seasonal Variations in Nitrogen Leaching and Acidity across Four Acid-impacted Regions of the UK

Abstract: This study examines the seasonal variability in levels of nitrogen (N) leaching and acidity in four acid impacted upland regions of the UK: the South Pennines, Snowdonia, Galloway and the Mourne Mountains. All regions are acidified, with median pH values of <5.5. The South Pennines exhibit excess sulphate concentrations an order of magnitude higher than those for other regions and have the lowest pH values of all the regions. Nitrate concentrations are highest in the South Pennines (seasonal medians 20-26 μeq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
4
16
0
Order By: Relevance
“…In warmer months, the biological uptake of NO − 3 by plants and microbes both in the terrestrial and aquatic systems is at its highest, immobilising NO − 3 . In winter, productivity declines, increasing the amount of NO − 3 available to be leached into the stream and its residence time in the stream (Black et al, 1993;Chapman et al, 2001;Helliwell et al, 2007b). The summer peaks in June and July 2010 are unusual and different to the summer lows observed in 2009.…”
Section: Seasonal Patterns Of N In Stream Watermentioning
confidence: 97%
“…In warmer months, the biological uptake of NO − 3 by plants and microbes both in the terrestrial and aquatic systems is at its highest, immobilising NO − 3 . In winter, productivity declines, increasing the amount of NO − 3 available to be leached into the stream and its residence time in the stream (Black et al, 1993;Chapman et al, 2001;Helliwell et al, 2007b). The summer peaks in June and July 2010 are unusual and different to the summer lows observed in 2009.…”
Section: Seasonal Patterns Of N In Stream Watermentioning
confidence: 97%
“…Differing from the declining atmospheric SO 4 2-deposition, nitrogen deposition changed little in North America, in fact it has increased slightly in the last decade (Driscoll et al 2003a;Jeffries et al 2003;Helliwell et al 2007). Nitrogen cycling, a function of plant uptake and microbial activities control net annual nitrogen retention or export within a watershed (Dow and DeWalle 1997;Williard et al 1997;Chapman et al 2001;Judd et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, high flow rates (such as floods) will tend to flush out many benthic invertebrates, whether the conditions are acidic or not (Dobson and Frid, 1998;Thornton, 2008 A number of recent studies have provided evidence for the importance of such extreme events. Helliwell et al (2007) found marked seasonality in their survey of nitrate levels and acidity in four upland areas of UK, including Galloway. Lepori and Ormerod (2005) reported that in episodically acidified streams survival (of species of Acid Sensitive Ephemeroptera) was the same as with matched circumneutral streams during periods of low flow, but substantially lower during episodes of high flow (during Alpine spring floods), when acidity increased significantly.…”
Section: The "Episodicity" Hypothesismentioning
confidence: 96%